ORIGAMI: AN ALTERNATIVE MEDIA TO TEACH PROCEDURE TEXT IN SPEAKING - Mitra, Muhammad Mujtaba (E-Link Journal, 2019)
Procedure text is the text that has to be mastered by senior high school. The purpose of the text is to give a clue how to do something through some steps. The students should experience the lesson in order to help them to know that activity is on their daily life and to apply the worldly education "learning to do" and to make class more lively and communicative. Experiencing the objective above, there are many kinds of media that can be used to motivate the students to learn procedure text orally. One of them is using "origami" (it's the art or process, originating in Japan, of folding paper into shapes representing objects such as flowers, animal and furniture etc.). This study is conducted using a descriptive qualitative research with non-participant researcher. The subject is the students of senior high school in Mojokerto. In doing the observation, the data are collected by observing the activity during the class, the result of observation checklist and the result of questionnaire. Using "origami" as an alternative media to teach procedure text in speaking class is expected to attract the students' interest; it can give the students' opportunities to feel a variety in teaching learning process. "Origami" helps the students increase motivation, enthusiasm, and become easy to practice their language orally. In carrying out "origami", the teacher selects "origami" for beginner because the models can be found in around their house or school. They enable the students to instruct orally. "Origami" is a good media in learning procedure text orally because it can give fun and relaxation and break up the routine class activity. Furthermore, the students experience and understand what they learn.Keywords: Origami, An alternative media, Procedure text, Speaking class